Symptom-based patient-reported outcomes in adults with eosinophilic esophagitis: value for treatment monitoring and randomized controlled trial design. Issue 2 (April 2019) - Safroneeva, Ekaterina; Schoepfer, Alain M.
Abstract : Purpose of review: In adults with eosinophilic esophagitis (EoE), a chronic, inflammatory immune-mediated condition of the esophagus, both inflammation and fibrosis are likely associated with symptom generation. Therefore, assessing symptom-based patient-reported outcomes (PROs), defined by US Food and Drug Administration as 'any report of the status of a patient's health condition that comes directly from the patients, without interpretation of the patient's response by a clinician or anyone else', is important in the context of trials and observational studies of emerging therapies. Recent findings: For purposes of treatment monitoring, lack of symptoms does not predict the absence of biologic inflammation; hence, endoscopy with esophageal biopsies should be performed to check for residual inflammation. Lack of inflammation does not predict lack of symptoms, and the presence of subepithelial fibrosis cannot be excluded. No published instrument currently measures the frequency of dysphagia described all possible ways, strategies of living with this symptom and various pain types. In randomized controlled trials, in which symptom response was detected using validated PRO measures, only modest decreases in symptom scores were observed. Summary: Accessing full EoE symptom spectrum and optimizing PRO measures remains a challenge that should be tackled to reliably assess response to existing and emerging therapies.